Multisensory Interior Design Interventions To Reduce Stress In High-Intensity Healthcare Settings - Kamel; Sellaoui (International Journal of Graphic Design, 2025)
The growing global emphasis on patient-centered care highlights a persistent gap in healthcare design: clinical environments often remain sterile and stress-inducing, undermining psychological recovery. This study introduces a human-centered, multisensory interior design framework that integrates sensory experience as a therapeutic variable rather than an aesthetic supplement. Unlike previous evidence-based or biophilic design studies that examine isolated sensory factors, this research validates an integrated multisensory model through mixed-method investigation. The study combines a systematic literature review, expert consultations with architects, designers, and healthcare professionals, and a quasi-experimental case study across three hospital wards implementing sensory-based interventions. Findings indicate that deliberately orchestrating visual, auditory, tactile, and olfactory stimuli significantly reduces patient anxiety, enhances perceived comfort, and improves staff well-being. Statistical results (paired t-tests and ANOVA) corroborate these effects, with measurable physiological and perceptual outcomes. The proposed framework translates these insights into actionable design strategies that align aesthetics with therapeutic evidence. This research advances interior architecture scholarship by bridging neuroscience, environmental psychology, and design practice, positioning multisensory design as a restorative paradigm for future healthcare environments.